Mythological and Fictional Color of Contemporary Urdu Poem of Baluchistan - DR. QANDEEL BADER (دریافت)
After the formation of language, the first link of human mind and civilization is the establishment of mythology. It would not be wrong if mythology is said to be the oldest form of literature in the world. Mythological style of expression is closely related to the genre of poem.